Biological parameters of Luciobarbus callensis populates Beni-Haroun dam, north-eastern Algeria - Houda Berrouk; Fatiha Sahtout; Chahinez Boualleg (Society for Indonesian Biodiversity, 2020)
The fish age and growth data mainly assist many ichthyologists to understand the life history features of species and population. The growth is a major process of fish biology, and considered as one of the key processes of length-structured models of fishes. Thus,   the present study was devoted to studying the growth of an autochthonous species (Luciobarbus callensis), populating the dam of Beni-Haroun (Mila city, northeast Algeria), and is known by its socio-economic value and aquaculture interest. The study was conducted on a sampling of 257 fish individuals during the year 2015 – 2016. The age of Luciobarbus callensis was determined by using the described method or the scalimetry method, providing an easier sampling and reading procedures, and also a high precision.  Fish sexes were identified via the observation of gonads, by naked eye based on gonad shape and color, where the number of females was higher (165) than males (92). The obtained results revealed a maximum longevity as seven years of Luciobarbus callensis, and the determined growth parameters of the separated and combined fish sexes were found to be as follow: L?= 47,37  cm ; K= 0,29  ; t0= -0,51  ; Ø’= 2,813 (females); L?= 42,11  cm ; K =0,26  ; t0= -0,58 ; Ø’= 2,663 (males); and  L?= 47 37  cm ; K= 0,20 ; t0= -0,75 ;  Ø’ =2,652 (combined sex). Moreover, the evolution of the total weight of fishes with respect to their size presents a minor allometry (b<3), (with or without sex distinction).